Effectiveness of social and therapeutic horticulture for reducing symptoms of depression and anxiety: a systematic review and meta-analysis - Wood, Carly J.; Barton, Jo; Wicks, Claire L. (Frontiers in Psychiatry, 2025)
BackgroundDepression and anxiety are the two most common mental health conditions, that often co-exist and relapse over time. There is a need for sustainable treatment options to address increasing rates of depression and anxiety and reduce the strain on health systems. Social and Therapeutic Horticulture (STH) is a nature-based health intervention that can reduce symptoms of depression and anxiety, however synthesised evidence of its effectiveness is required to inform commissioning and availability of interventions.AimThe aim of this systematic review and meta-analysis was to examine the effectiveness of STH for reducing symptoms of depression and anxiety.MethodFollowing PRISMA guidelines and the protocol registered on Prospero (CRD42024542671) a systematic search of scientific databases and grey literature was conducted to identify quantitative studies examining the impact of STH interventions on depression and anxiety outcomes. Studies were eligible for inclusion if they reported on an STH intervention that was led by a trained practitioner, administered to adult populations who were identified as either at risk, with symptoms or diagnosis of depression and/or anxiety and reported on depression or anxiety outcomes measured using validated scales. Data from eligible studies were extracted and analysed using a random effects meta-analysis.ResultsSeventeen studies were identified for inclusion including four RCTs, ten quasi-experimental studies with comparators and three single group studies. Nine studies reported outcomes for depression only, two for anxiety only and six for both depression and anxiety. Across studies with comparators, meta-analyses revealed large and significant effects in favour of the STH group for depression (SMD= -1.01; p=<.001) and moderate and significant effects in favour of the STH group for anxiety (SMD=-.62; p<.001). There was significant heterogeneity across studies, with high risk of bias, particularly for statistical validity and outcome measure reliability.ConclusionsSTH interventions have the potential to support existing treatment approaches for depression and anxiety. However, to inform commissioning and upscaling of services, rigorous randomised studies comparing STH to treatment as usual for depression and anxiety are required.